Ghost Discrimination Method for Broadband Direct Position Determination Based on Frequency Coloring Technology - Mengling Yu; Long Yang; Yixin Yang; Xionghou Liu; Lu Wang (Journal of Marine Science and Engineering)
Recently proposed direct position determination (DPD) methods have garnered considerable interest in passive localization due to their excellent positioning accuracy. However, in multiple-target environments, error locations generated by wrong associations between different targets and arrays, called ghosts, may lead to incorrect estimations of the targets, reducing positioning accuracy. To address this, we propose a ghost discrimination method for broadband DPD that exploits the frequency structure differences between various targets. In the frequency coloring strategy proposed in this study, different RGB values are assigned to the spatial spectrum of different frequencies. Then, an RGB color spatial spectrum reflecting the different frequency structures of the signals is formed, which effectively distinguishes between real targets and ghosts visually and enhances multi-target localization accuracy. The probability of correctly distinguishing between targets and ghosts in the proposed method is evaluated using simulation results. It can effectively distinguish multiple targets even at a low SNR level, a significant improvement compared with the original DPD. Furthermore, the SwellEx-96 shallow-water experimental data set is utilized to demonstrate the effectiveness of the proposed method.